A dispersive magnetic solid phase microextraction based on ionic liquid-coated and cyclodextrin-functionalized magnetic core dendrimer nanocomposites for the determination of pyrethroids in juice samples. (1st December 2018) - Liu, Fang; Yang, Xiaoling; Wu, Xiaoling; Xi, Xuefei; Gao, Haixiang; Zhang, Sanbing; Zhou, Wenfeng; Lu, Runhua
Highlights: The nanocomposites possess both the selective retention of guest dendrimer and cyclodextrin molecules and high adsorption capacities of ionic liquids. A d-MSPE method based on ionic liquid-coated and cyclodextrin-functionalized magnetic core dendrimer nanocomposites has been developed to determine pyrethroids in real juice samples. The nanocomposites were proved to broaden the potential for PAMAM as a novel sorbent and the method showed acceptable extraction performance. Abstract: A novel dispersive magnetic solid phase microextraction method based on ionic liquid-coated and cyclodextrin-functionalized magnetic core dendrimer nanocomposites has been developed for the determination of pyrethroids in juice samples. The different generation magnetic core dendrimer nanocomposites were successfully synthesized and the nanocomposites possess both the selective retention of guest dendrimer and cyclodextrin molecules and high adsorption capacities of ionic liquids. The extraction efficiencies of different generation magnetic core dendrimer nanocomposites were compared, and the type of nanocomposite with the highest recovery was obtained. Under the optimized experimental conditions, the method showed good linearity in the range of 3.5–500 μg L −1 . The LODs and LOQs were in the ranges of 0.36–1.3 μg L −1 and 1.2–4.3 μg L −1, respectively. The method also showed acceptable accuracies ranging from 98.2% to 99.4%. The proposed method was demonstrated to broaden the potential applications of dendrimer for the detection of pyrethroid residues in various juice samples.